Valoración prequirúrgica en pacientes programados para cirugías, Hospital San Vicente de Paúl 2017: Pre surgical checkup in patients with programed surgery, San Vicente de Paúl hospital 2017 (La U Investiga, 2019)
All the patients need to have an evaluation of their health status before a surgery, this one has to be performed by a physician and supported by complementary exams. It has been made a cross-sectional study with a sample total of 552 patients. The data were obtained from the medical records of patients who get into Traumatology and General Surgery service in the period of time between January and July of 2017. The information was processed and analyzed with the statistical program SPSS IBM version 23.0. Of the 552 clinical records reviewed, 212 cases (38,4%) had a pre surgical checkup, while 61,6% had no previous surgical checkup. Was found a statistical significance between age and the compliance of the surgical checkup, this because the higher prevalence was found in patients greater that 59 years old representing an 22,83%. The laboratory and image exams in 11.4% of the sample were justified on the basis of the patient’s condition because they influenced in the course of the surgery, also there was a great expense because of the request of exams without justification, being the most requested and expensive the blood chemistry. Finally we can conclude that the preoperative management performed in those patients, do not have all the parametersto perform a correct preoperative checkup.
Keywords: Preoperative checkup; routine exams; scheduled surgeries